The Role of the Pentose Phosphate Pathway in Diabetes and Cancer - Ge, Tongxin; Yang, Jiawen; Zhou, Shihui; Wang, Yuchen; Li, Yakui; Tong, Xuemei (Frontiers in Endocrinology, 2020)
The pentose phosphate pathway (PPP) branches from glucose 6-phosphate (G6P), produces NADPH and ribose 5-phosphate (R5P), and shunts carbons back to the glycolytic or gluconeogenic pathway. The PPP has been demonstrated to be a major regulator for cellular reduction-oxidation (redox) homeostasis and biosynthesis. Enzymes in the PPP are reported to play important roles in many human diseases. In this review, we will discuss the role of the PPP in type 2 diabetes and cancer.